PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASILBELAJAR IPS SISWAKELAS IV SD NEGERI 56 PEKANBARU - Yanti, Desi Fitri; Lazim N, Lazim N; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstrakThe study was based on the low learning outcomes of SD Negeri 56 Pekanbaru on fourth grade students. From 30 students who achieved KKM only 10 students. The purpose of this research is to improve the learning outcomes of the students of fourth grade students in SD Negeri 56 Pekanbaru with the application of contextual learning model. The results of the activity of the teacher 's in first meeting of the first cycle percentage of 50% with less categories, improved in the second meeting be fairly categorized 56.25%. At the first meeting of the second cycle increased with the percentage of 62.50% with enough categories and at the second meeting of the second cycle of 68.75% categorized good. At the first meeting of the third cycle increased with the percentage of 81.25% with a very good category and at the second meeting of the third cycle increased to 87.50 categorized very well. In the first cycle, the first meeting of the first cycle percentage 50% less category, rising at the second meeting of the percentage of 56.25 % categorized good. At the first meeting of the second cycle increased to 62.50 categorized good. At the first meeting of the third cycle increased to 75% categorized very well, and at the second meeting of the third cycle increased to 87.50 categorized very well . Mastery learning students on the basis of scores of students who completed the 10 students who did not complete while 20 students, with classical completeness 33.33 % not finished). At the end of the first cycle of repeat students who complete 18 incomplete whereas 12 students, with classical completeness 60 % (not finished) . At the end of the second cycle replications increased thoroughness, students who completed the 21 students who did not complete whereas 9 students, with classical completeness 70% (not finished) . At the end of the replication cycle III also increased the thoroughness of students who completed 30 students, while students who do not complete 0, the classical completeness 100% (completed) .Keywords: Kontekstual, The Result Of Social Studies1.